THE EFFECT OF OBESITY ON CHILDREN FITNESS IN THE AGE 10-12 YEARS OLD - Indra Lesmana, Syahmirza; Fariha Fuadi, Dela; Chalik Meidian, Abdul; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of this study was to determine the differences in fitness among 10–12-year-old students with normal body mass index and obesity. Methods: This study was quantitative descriptive, which to determine the differences in fitness among 10–12-year-old students especially in cardiorespiratory fitness. Cardiorespiratory fitness was measured by indirect method use prediction formula for Volume Oxygen Maximum (VO2max). Normality test uses Shapiro wilk test. The sample consisted of 30 students which divided into two groups, first group consisted of 15 students with normal body mass index and another group consisted of 15 students with obesity. Result: Normality test was tested by Shapiro Wilk Test showed that the data is distributed abnormal with the result p=0,012 (p